From “paralysing myths” to curriculum expansion: Boundaries, spaces and territories and the place of new technologies - Melvin, Jane (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2014)
The use of digital tools within youth work contexts contributes to improved outcomes for young people such as increased communication, information-sharing, conversation and discussion, creativity, campaigning, networking, participation and agency, as well as promoting digital literacy at a number of levels. Online social networks are becoming a tool for connecting people, hosting conversation and social interaction, and supporting collaboration. They should surely be an extension of what the youth worker already does on a face-to-face level. This paper will explore whether youth workers should seek to be included in the online spaces that young people inhabit, where the boundaries should be, and whether current moral panics focused towards new technologies that are oriented towards violence, stereotyped, commercially exploitive or pornographic content and about the reinforcement of individualistic, lazy, prejudiced, uncritical or aggressive activities, are a stimulus for avoidance or action.